PENGARUH EFEKTIFITAS PENGENDALIAN INTERNAL DAN KESESUAIAN KOMPENSASI TERHADAP PENCEGAHAN KECURANGAN (FRAUD) PADA PDAM TIRTA SIAK PEKANBARU - Cita Cendikia; Almasdi Syahza; Fenny Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : One of the way to improve the performance of a company is to prevent fraud that will be in the future. Therefore we need an effective of internal control to able to control and supervise any activity in that company. As well as adjustments of compenssation granted to employees to reduce the employees to act fraudulently adverse. Data for this study was obtained by questioner to all permanent employees of PDAM Tirta Siak Pekanbaru that are 96 repondents. Data analysis technique used are normality test, regression, F-test, coefficient detemination analysis and T-test. The results showed that (1) Simultaneously, there were influence between the effectiveness of internal control and compensation compatibility on fraud prevention with significant value 0,002 (below 0,05). The coefficient of determination in this research are 13,5%, both variable jointly influence dependent variable, while 86,5% is influenced by other unclear variable. (2) There were influence between effectiveness of internal control on fraud prevention with significant value 0,006 (below 0,05) and (3) There were no influence between compensation compatibility on fraud prevention with significant value 0,137 > 0,05.Keywords : Internal Control , Compensation Compatibility , Fraud Prevention